2020
DOI: 10.1093/pm/pnaa321
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Invasive Techniques in Patients with Fibromyalgia: Systematic Review and Meta-Analysis

Abstract: Objective To attain a synthesis of the evidence on the effectiveness of invasive techniques in patients with fibromyalgia, through systematic review and meta-analysis and by assessing the methodological quality of the studies considered. Methods A systematic review and meta-analysis were carried out as defined in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. The bibliographic resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
4
0
2
Order By: Relevance
“…Although this is not the first meta-analysis comparing the application of dry needling and acupuncture for reducing pain and disability in patients with FM [ 64 ], the existing literature included a minor number of articles (including 14 studies for qualitative synthesis and 8 in the quantitative synthesis) and outcomes (i.e., FIQ, PPT and quality of life) in their analyses compared with this one, despite all types of invasive techniques being compared in their analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Although this is not the first meta-analysis comparing the application of dry needling and acupuncture for reducing pain and disability in patients with FM [ 64 ], the existing literature included a minor number of articles (including 14 studies for qualitative synthesis and 8 in the quantitative synthesis) and outcomes (i.e., FIQ, PPT and quality of life) in their analyses compared with this one, despite all types of invasive techniques being compared in their analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found fascia of patients with myofascial pain measures statistically significantly higher on shear wave elastography, and they have increased peri-muscular connective tissue thickness and ultrasound echogenicity [241,242]. It was found that needling treatment reduces pain [243][244][245][246][247]. Studies suggest needling significantly lowers the shear modulus of myofascial tissue as measured by elastography (p-value <0.01) [95], causes mechanical changes at the point of insertion and at a distance [91,102], causes windup of the connective tissue [105], and improves perfusion to the area [248].…”
Section: Plos Onementioning
confidence: 99%
“…Some studies found fascia of patients with myofascial pain measures statistically significantly higher on shear wave elastography, and they have increased perimuscular connective tissue thickness and ultrasound echogenicity [241,242]. It was found that needling treatment reduces pain [243][244][245][246][247]. Studies suggest needling significantly lowers the shear modulus of myofascial tissue as measured by elastography (p-value <0.01) [95], causes mechanical changes at the point of insertion and at a distance [91,102], causes windup of the connective tissue [105], and improves perfusion to the area [248].…”
Section: Compression Versus a Global Percutaneous Needle Fasciotomy: Conclusionmentioning
confidence: 99%